ANALISIS KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK SMK HIDAYATUL MUBTADI’IEN PADA MATERI GERAK LURUS - Endah Dwi Haryati; Stepanus Sahala Sitompul; Hamdani Hamdani (Universitas Tanjungpura, 2021)
AbstractThe study aims to determine the students’ problem-solving ability of class X in SMK Hidayatul Mubtadi'ien on straight motion material. The study used a survey method involving 23 students of class X. The students’ problem-solving ability was measured using a test instrument of 5 description questions. Based on the data analysis, it was found that the average percentage of students' problem-solving abilities in aspect A, namely the ability to process problems, was 21.52% (less category), the percentage in aspect B, namely the ability to describe problems, was 36.74% (less category), the percentage in aspect C, namely the ability to plan solutions by 29.35% (poor category). Then, the percentage in aspect D, namely the ability to implement solution plans, 25.87% (poor category), the percentage in aspect E, namely the ability to evaluate solutions, is 7.83% (very poor category). Thus, the overall percentage of students' problem-solving abilities is 24.26% (less category). In the independent t-test results obtained Asym.sig 2-Tailed of 0.377 (> 0.05), it was concluded that there had not been any significant difference in problemsolving ability between male and female students. The study is expected to be used as a reference in improving students' problem-solving abilities in straight motion material.Keywords: Gender, Problem-solving Ability, Straight Motion